Prevalence of Impacted Teeth among the Orthodontic Patient in Bangabandhu Sheikh Mujib Medical University - Nahar, Luthfun; Jha, Digamber; Hassan, Gazi Shamim (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Aim: This study was attempted to find out the prevalence of impacted teeth among the patients attended for orthodontic treatment in Bangabandhu Sheikh Mujib Medical University Materials and Method: For this cross sectional study 200 patients were taken according to selection criteria who were seeking orthodontic treatment, age between 10 and 30 years in Bangabandhu Sheikh Mujib Medical University. Results: 42.0 % respondents belong to age group 11-15 years, 65.5% respondents were female and 34.5% were male, who had impacted teeth with other orthodontics problems. Among 3.0% respondents 1.5 % showed impaction in right upper central incisor and other showed impaction in right upper canine, in left upper central incisor and also left upper canine. The prevalence of impacted teeth was not significant for age group ( p=0.449) and there was no significant difference between male and female (p=0.695). Conclusion: The prevalence of tooth impaction is a common dental anomaly. The early recognition of tooth impaction is very important from a therapeutic point of view. Ban J Orthod & Dentofac Orthop, April 2015; Vol-5 (1-2), P.24-26